Multiple linear regression analysis between thermal comfort and worshippers’ satisfaction in Malaysian Mosque / Nur Hanan Safee and Asniza Hamimi Abdul Tharim - Safee, Nur Hanan; Abdul Tharim, Asniza Hamimi (2019)
Human thermal comfort is the paramount target to achieve the satisfaction of the occupation and users of the building. However, in Malaysia daily climate with high air temperature and relative humidity and inconsistent air movement throughout the day affect the thermal comfort for the building. Inappropriate thermal comfort in mosque buildings will lead to the unsuitable thermal environment for the worshippers and the function held inside of the building. Therefore, the objective of this paper is to determine worshippers' satisfaction level toward thermal comfort condition in Malaysia mosques. This study used a quantitative method in research methodology by a measure of the questionnaire survey and was conducted in Kelantan Darul Naim Malaysian Mosque. Then, the survey evaluated by using SPSS Version 23.0. Based on data, the most dominant factor that influences worshippers' satisfaction is air movement in mosques building. From this study, it is hoped that this study will give benefit in term of the worshipper's satisfaction towards thermal comfort in mosques building.